Revolutionizing the Digital Creative Industries: The Role of Artificial Intelligence in Integration, Development, and Innovation - Wagan, Shah Mehmood; Sidra, Sidra (SEISENSE Journal of Management, 2024)
Purpose - Artificial intelligence is profoundly transforming the digital creative industry, becoming a key force in industrial upgrading through technology integration, innovation drive and productivity improvement. Methods- This study uses a variety of methods, including literature review, questionnaire survey, in-depth interview and data analysis, to systematically examine the application effect of AI in the digital creative industry. The structural equation model is used to verify the hypothesized relationship, and the role of AI in promoting industrial integration, development results and innovation catalysis effect are comprehensively analyzed. Research results- The research that AI importantly promotes technological integration, development and innovation inside the digital creative industry, and improves the general overall performance of the industry. The path coefficient is incredibly substantial, and the model fit is good, which verifies the effective position of AI in industrial integration and development. The position of AI not only improves the competitiveness of the industry, but also provides robust support for the personalization and excessive quality of creative products. Originality- This paper demonstrates remarkable originality in theoretical framework construction, empirical data analysis, and exploration of practical challenges and this paper deeply analyzes the multiple mechanisms of AI in the digital creative industry, providing new ideas and specific quantitative evidence for research in related fields. Implications - Practitioners need to actively accept AI era, optimize creative workflows, and enhance production efficiency and constantly enhance their digital talents and cross-area information integration capabilities. Policymakers should formulate focused support policies to promote the vast application and deep integration of AI technologies inside the creative industries.